The problems of the modern world monetary system (Journal of Economic Research & Business Administration, 2016)
The global monetary system has evolved in several successive stages. Each of them is characterized first of all by a definite form of global reserve assets. These reserve assets provide the turnover of all world trade and are a universal means of payment, savings and measure of value. At different stages of the functioning of the world monetary system the role of money carried gold and national currencies of some developed countries of the West. These currencies were recognized as a standby, because monetary gold reserves of the world were nominated in them. Moreover, the value of international contracts is determined with the use of reserve currencies, Reserve currencies are the tool of currency interventions and the basis of monetary and exchange rate policies of many countries. [1] Modern monetary system is characterized by instability of the exchange rate of the main reserve currency – the US dollar.